Idiopathic Macular Hole: A Comprehensive Review of Its Pathogenesis and of Advanced Studies on Metamorphopsia - Chen, Qi (J Ophthalmol, 2019)
Vitreous anteroposterior traction is an important factor that affects macular hole (MH) formation at the early stage, and vitreous tangential traction can lead to further hole expansion after hole formation. Recent studies have highlighted the significance of Müller cells for the pathogenesis of MH. Since the advent of MH treatment, success rates for MH closure have significantly improved, as has postoperative visual acuity. However, metamorphopsia, an initial and common symptom of MH, still exists. Metamorphopsia is significantly related to the deterioration of visual quality of life and can be used as an independent index to evaluate visual function before and after surgery. In MH patients, metamorphopsia has different manifestations representing different clinical implications. M-CHARTS, as a new means of inspection, can quantify the degrees of metamorphopsia, and with the development of optical coherence tomography (OCT), layer-by-layer scanning of the retinal structure has become possible. These methods enable detailed analysis of the connections between the degree of metamorphopsia and relevant OCT parameters. Preoperative OCT parameters can be used to evaluate the prognosis of the postoperative visual function of MH patients and are therefore of great significance in guiding the treatment of MH patients.